2015
DOI: 10.1124/dmd.115.064949
|View full text |Cite
|
Sign up to set email alerts
|

Human Liver Cytochrome P450 Enzymes and Microsomal Thiol Methyltransferase Are Involved in the Stereoselective Formation and Methylation of the Pharmacologically Active Metabolite of Clopidogrel

Abstract: Clopidogrel, a thienopyridine antiplatelet prodrug, is metabolized by oxidation to 2-oxo-clopidogrel, followed by conversion to its pharmacologically active thiol metabolite. After oral administration of clopidogrel to humans, two thiol isomers (H3 and H4) are observed in plasma, with similar concentrations, and only H4 is active in humans. In this work, the mechanism of stereoselectivity in the formation and S-methylation of H3 and H4 was investigated in vitro. The two diastereomers of 2-oxo-clopidogrel were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…For instance, ABCA1 DNA methylation was a predictive biomarker for the CAD development and was independent of plasma lipid concentration . Since 2014, several studies have explored the influence of DNA methylation in ABCB1 , P2Y12 , and cytochrome P450 enzymes on CR. This time, we chose PON1 as the target gene and found some significant results.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ABCA1 DNA methylation was a predictive biomarker for the CAD development and was independent of plasma lipid concentration . Since 2014, several studies have explored the influence of DNA methylation in ABCB1 , P2Y12 , and cytochrome P450 enzymes on CR. This time, we chose PON1 as the target gene and found some significant results.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that, when the rats were pretreated with verapamil, the absorption of pristimerin was significantly increased. As verapamil has been reported to be an inhibitor of P‐gp and CYP3A (Gao et al ., ), we speculated that verapamil might increase the absorption of pristimerin by inhibiting P‐gp‐mediated drug efflux or CYP3A‐mediated metabolism because CYP3A is one of the most abundant drug‐metabolizing P450 isoforms in human liver microsomes, and almost 34.1% of drugs are metabolized by CYP3A (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, the formation of M1 and M14 was linear during the extended incubation time course, demonstrating that methyltransferase enzymes and SAM were thermally stable at 37°C up to 24 hours. Historically, incubation times for investigating methyltransferase activity in vitro range from 10 minutes to 2 hours (Van Loon et al, 1985;Kazui et al, 2014;Liu et al, 2015). From our work, it is noteworthy that, unlike cytochrome P450 enzymes, methyltransferase enzymes in microsomal or cytosolic preparations can be incubated at 37°C for 24 hours without the loss of enzyme activity.…”
mentioning
confidence: 93%
“…In Asians, TPMT activity is high with a unimodal distribution due to the lack of TPMT L allele (Jang et al, 1996). TMT is responsible for the S-methylation of captopril and ziprasidone, and, most recently, the S-methylation of the pharmacologically active metabolites of clopidogrel and prasugrel (Keith et al, 1984;Obach et al, 2012;Kazui et al, 2014;Liu et al, 2015). Although the gene that encodes TMT has yet to be identified, it was reported that TMT activity varies 5-fold among the Caucasian population (Keith et al, 1983b;Glauser et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation